The Implementation of Project-Based Learning to Improve Students’ Speaking Skill - Diki Riswandi (Universitas Jambi, Magister Program of English Education Department, 2018)
This study addresses specific teaching methods, which are believed to achieve a beneficial outcome to students’ learning ability. Project Based Learning is a modern teaching method. The core idea of Project Based Learning is to connect student's experiences with school life and to provoke students to acquire new knowledge. This study aims at (1) describing to what extent the use of Project-based Learning can improve the students' speaking skill and (2) describing the teaching and learning process when Project-Based Learning is implemented in the class. The subject of the study is the seventh-grade students of one of Junior High Schools in Surakarta. The method of the study was classroom action research with two cycles. Furthermore, the data were collected through speaking assessment. The finding showed that there was improvement in the students' speaking skill. Some aspects which are improved including students' fluency, vocabulary, pronunciation, grammar, and comprehension. To conclude, PBL (Project-based learning) help student in improving their speaking skill.